Overweight and Obesity Among Children Between 9.12 years "crosssectional study" (Eurasian Medical Research Periodical, 2023)
"Overweight" technically refers to an excess of body weight, whereas "obesity" refers to an excess of fat.Childhood obesity is a growing problem and an increasing public health concern in the developed countries. Even more worrying is the increasing prevalence of obesity in developing countries. Childhood obesity is a well-recognized problem all over the world. Obesity can cause other medical problems in childhood, adolescence and adulthood.